Carotenoids promote lateral packing and condensation of lipid membranes. Issue 21 (20th May 2020) - Mostofian, Barmak; Johnson, Quentin R.; Smith, Jeremy C.; Cheng, Xiaolin
Abstract : Carotenoids, pigment molecules that protect biomembranes against degradation, are shown to have similar effects to cholesterol on regulating the behavior of fluid-phase membranes. Abstract : Carotenoids are pigment molecules that protect biomembranes against degradation and may be involved in the formation of functional bacterial membrane microdomains. Little is known on whether different types of carotenoids have different effects on the membrane or if there is any concentration dependence of these effects. In this work, we present results from molecular dynamics simulations of phospholipid bilayers containing different amounts of either β-carotene or zeaxanthin. Both β-carotene and zeaxanthin show the ability to laterally condense the membrane lipids and reduce their inter-leaflet interactions. With increasing concentrations, both carotenoids increase the bilayer thickness and rigidity. The results reveal that carotenoids have similar effects to cholesterol on regulating the behavior of fluid-phase membranes, suggesting that they could function as sterol substitutes and confirming their potential role in the formation of functional membrane domains.